2021
DOI: 10.1002/ente.202001059
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Resistive LiCoO2/Li1.3Al0.3Ti2(PO4)3 Interface Formation by Low‐Temperature Annealing Using Aerosol Deposition

Abstract: Interfacial resistance at electrode‐high Li+ conductive solid electrolytes must be reduced well to develop high‐power all‐solid‐state batteries using oxide‐based solid electrolytes (Ox‐SSBs). Herein, crystalline electrode films of LiCoO2 (LCO) are formed on a high Li+ conductive crystalline‐glass solid electrolyte sheet, Li1.3Al0.3Ti2(PO4)3 (LATP) (σ25 °C = 1 × 10−4 S cm−1), at room temperature by aerosol deposition (AD), and the effects of the annealing temperature on the interfacial resistivities (Rint) at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…However, the sintering of the reactive substances often results in undesired side reactions. [19][20][21][22][23][24] For example, a highly ion-conducting solid electrolyte, LATP and a high-capacity cathode material, LCO which is practically used in conventional liquid LIBs, fatefully react with each other to produce completely different species instead of forming a well-defined interface. 1,23 Although a few experimental results on the co-sintering products of LCO and LATP studied by XRD have been reported, [25][26][27] the main purpose of these previous reports was not the clarification of the reaction mechanism but fabrication of ASSLIBs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the sintering of the reactive substances often results in undesired side reactions. [19][20][21][22][23][24] For example, a highly ion-conducting solid electrolyte, LATP and a high-capacity cathode material, LCO which is practically used in conventional liquid LIBs, fatefully react with each other to produce completely different species instead of forming a well-defined interface. 1,23 Although a few experimental results on the co-sintering products of LCO and LATP studied by XRD have been reported, [25][26][27] the main purpose of these previous reports was not the clarification of the reaction mechanism but fabrication of ASSLIBs.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] For example, a highly ion-conducting solid electrolyte, LATP and a high-capacity cathode material, LCO which is practically used in conventional liquid LIBs, fatefully react with each other to produce completely different species instead of forming a well-defined interface. 1,23 Although a few experimental results on the co-sintering products of LCO and LATP studied by XRD have been reported, [25][26][27] the main purpose of these previous reports was not the clarification of the reaction mechanism but fabrication of ASSLIBs. Hence, co-sintering was performed only for short periods of time (1-2 h) to form well-defined interfaces with a relatively high ion-conductivity while avoiding or minimizing the undesired reaction between LCO and LATP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many available deposition technologies for thin film growth, including sol-gel method, [301][302][303][304] inkjet printing, [305,306] rf-sputtering, [174,206,210,229,230,258,307,308] plasma spray PVD (PS-PVD), [309] PLD, [310,311,312] chemical vapor deposition (CVD), [313] aerosol deposition, [314] ion-beam assisted deposition, [315] and ebeam evaporation. [316] The review article by Lobe et al [308] well documented various deposition technologies.…”
Section: Technologies For Thin-film 𝝁-Batteriesmentioning
confidence: 99%
“…The conventional manufacturing process to obtain the oxide-based solid electrolyte/electrode material interfaces is sintering at high temperatures , because those materials have a high melting point and poor plasticity. However, co-sintering of oxide-based solid electrolytes and electrode materials often results in undesirable side reactions. For example, sintering the mixture of highly Li-ion-conducting NASICON-type solid electrolytes (LiM 2 (PO 4 ) 3 ) and layered rock salt-type (LiMO 2 ) or spinel-type lithium metal oxides (LiM 2 O 4 ) often induces severe side reactions. In our previous study, we found that a NASICON-type solid electrolyte, Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 (LATP), and a layered rock salt-type cathode material, LiCoO 2 , commonly used in conventional liquid LIBs, reacted with each other to produce various species rather than forming a well-defined interface, even at 300 °C …”
Section: Introductionmentioning
confidence: 99%